VATS therapy of chylothorax caused by leiomyomatosis complicated with tuberous sclerosis complex - Csiszkó, Adrienn (Medknow Publications & Media Pvt Ltd, 2013)
Lymphangioleiomyomatosis with tuberous sclerosis complex is a rare disease. One of the most frequent complications of lymphangioleiomyomatosis is pleural effusion (chylothorax) wich can be treated with the use of VATS. Authors report a case of pulmonary lymphangioleiomyomatosis in a 56-year-old female patient with tuberous sclerosis complex with an 8-week history of recurrent chylothorax, dyspnea and debilitating weakness. By CT scan a flat tissue proliferation was seen in the site of the thoracic duct and it was supposed to be the reason for the pleural effusion. A VATS resection of this laesion and ligation of the thoracic duct was performed successfully. Chylothorax is often associated with pulmonary lymphangioleiomyomatosis. Lymphangioleiomyomatosis combined with tuberous sclerosis complex is extremely rare. In case of chylothorax VATS treatment is successful and may be the first choice.